The reasoning criminal vs. Homer Simpson: conceptual challenges for crime science - Bouhana, Noemie (Frontiers in Human Neuroscience, 2013)
A recent disciplinary offshoot of criminology, crime science defines itself as “the application of science to the control of crime.” One of its stated ambitions is to act as a cross-disciplinary linchpin in the domain of crime reduction. Despite many practical successes, notably in the area of situational crime prevention, crime science has yet to achieve a commensurate level of academic visibility. The case is made that the growth of crime science is stifled by its reliance on a model of decision-making, the Rational Choice Perspective, which is inimical to the integration of knowledge and insights from the behavioural, cognitive and neurosciences (CBNs). Examples of salient developments in the CBNs are provided, as regards notably multiple-system perspectives of decision-making and approaches to person-environment interaction. Short and long-term benefits of integration for crime science are briefly outlined.